Cell-Penetrating Peptide-Modified Graphene Oxide Nanoparticles Loaded with Rictor siRNA for the Treatment of Triple-Negative Breast Cancer - Yang YY; Zhang W; Liu H; Jiang JJ; Wang WJ; Jia ZY (Dove Medical Press, 2021)
Yun-Yun Yang,1 Wei Zhang,2 Hui Liu,2 Jun-Jie Jiang,2 Wen-Jie Wang,3 Zheng-Yan Jia4 1Outpatient Comprehensive Treatment, Cangzhou Central Hospital, Cangzhou, Hebei Province, People's Republic of China; 2Department of Thyroid and Breast I, Cangzhou Central Hospital, Cangzhou, Hebei Province, People's Republic of China; 3Department of General Surgery, Botou Hospital, Cangzhou, Hebei Province, People's Republic of China; 4Department of General Surgery, Qingxian People's Hospital, Cangzhou, Hebei Province, People's Republic of ChinaCorrespondence: Wei ZhangDepartment of Thyroid and Breast I, Cangzhou Central Hospital, Cangzhou, Hebei Province, People's Republic of ChinaEmail weiesiz685125@163.comIntroduction: Breast cancer is a malignant tumor that seriously threatens women's life and health.Methods: In this study, we proposed to use graphene nanoparticles loaded with siRNA that can silence Rictor molecules essential for the mammalian target of rapamycin (mTOR) complex 2 (mTORC2) complex to enhance gene delivery to tumor cells through modification of cell-penetrating peptide (CPP) for the treatment of breast cancer.Results: Remarkably, we successfully synthesized graphene oxide (GO)/polyethyleneimine (PEI)/polyethylene glycol (PEG)/CPP/small interfering RNA (siRNA) system, and the results were observed by atomic force microscopy (AFM) and ultraviolet visible (UV-Vis) absorption spectra. The optimum mass ratio of siRNA to GO-PEI-PEG-CPP was 1:0.5. We screened out Rictor siRNA-2 from 9 candidates, which presented the highest inhibition rate, and this siRNA was selected for the subsequent experiments. We validated that Rictor siRNA-2 significantly reduced the Rictor expression in triple negative breast cancer (TNBC) cells. Confocal fluorescence microscope and flow cytometry analysis showed that GO-PEI-PEG-CPP/siRNA was able to be effectively uptake by TNBC cells. GO-PEI-PEG-CPP/siRNA improved the effect of siRNA on the inhibition of TNBC cell viability and the induction of TNBC cell apoptosis. The expression of Rictor and the phosphorylation of Akt and p70s6k were inhibited by GO-PEI-PEG-CPP/siRNA. Tumorigenicity analysis in nude mice showed that GO-PEI-PEG-CPP/siRNA significantly repressed the tumor growth of TNBC cells in vivo. The levels of ki-67 were repressed by GO-PEI-PEG-CPP/siRNA, and the apoptosis was induced by GO-PEI-PEG-CPP/siRNA in the system.Discussion: Therefore, we concluded that CPP-modified GO nanoparticles loaded with Rictor siRNA significantly repressed TNBC progression by the inhibition of PI3K/Akt/mTOR signaling. Our finding provides a promising therapeutic strategy for the treatment of TNBC.Keywords: triple-negative breast cancer, graphene oxide, cell-penetrating peptide, Rictor, PI3K/Akt/mTOR signaling